2017
DOI: 10.1103/physrevc.96.064903
|View full text |Cite
|
Sign up to set email alerts
|

Event-by-event correlations between soft hadrons and D0 mesons in 5.02 TeV PbPb collisions at the CERN Large Hadron Collider

Abstract: In this paper heavy quark energy loss models are embedded in full event-by-event viscous hydrodynamic simulations to investigate the nuclear suppression factor and the azimuthal anisotropy of D 0 mesons in PbPb collisions at √ sNN = 5.02 TeV in the pT range 8-40 GeV. In our model calculations, the RAA of D 0 mesons is consistent with experimental data from the cms experiment. We present the first calculations of heavy flavor cumulants v2{2} and v3{2} (and also discuss v2{4}), which is also consistent with expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 70 publications
(85 reference statements)
0
33
0
Order By: Relevance
“…The hadronization of the heavy quarks is performed either though fragmentation only (Peterson) [2], or through heavy-light quark coalescence. The latter is based on an instantaneous projection of the parton states onto hadron states [12,13], and the derived coalescence probabilities depend on the heavy-quark momentum, the local flow, and the angle between them.…”
Section: The Dab-mod Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The hadronization of the heavy quarks is performed either though fragmentation only (Peterson) [2], or through heavy-light quark coalescence. The latter is based on an instantaneous projection of the parton states onto hadron states [12,13], and the derived coalescence probabilities depend on the heavy-quark momentum, the local flow, and the angle between them.…”
Section: The Dab-mod Simulationmentioning
confidence: 99%
“…Observables in the heavyflavor sector such as the nuclear modification factor R AA and azimuthal anisotropy coefficients v n of D and B mesons have been investigated both experimentally and theoretically [1], and there is a certain difficulty to describe both R AA and v 2 simultaneously. Here we present the 2D Monte Carlo D-And-B MODular simulation code DAB-mod, designed to study the production of open heavy mesons [2]. Using DAB-mod we study heavy-flavor multiparticle cumulants of azimuthal anisotropies [3] and compare results from different transport models within the same background.…”
Section: Introductionmentioning
confidence: 99%
“…The v 3 signal is smaller than the v 2 and shows a weaker variation over centrality. Experimental data are also compared to prediction from TAMU (transport of the heavy-flavor within the QGP) [14] and DABMod (energy-loss of heavy-flavor in the QGP) [15] models. DABMod gives better a description of v 2 than TAMU probably due to implementation of the event-by-event fluctuations into the model.…”
Section: Pos(lhcp2019)222mentioning
confidence: 99%
“…In recent years it was found that a more realistic description of the QGP medium is a necessary tool for simultaneously reproducing the nuclear modification factor R AA and the high p T and heavy flavor azimuthal anisotropies v n {m}(p T ) [44,10,11,45]. Therefore we include a realistic event-by-event description of the medium coupled to modular heavy flavor code using Trento+v-USPhydro+DAB-MOD.…”
Section: Modelmentioning
confidence: 99%
“…The hydrodynamic model is v-USPhydro [48,49,50] where we use the same parameters for LHC run 2 as in [51] where τ 0 = 0.6 fm, η/s ∼ 0.05, and T FO = 150 MeV. To describe the heavy flavor sector we run DAB-MOD [45] a modular Monte Carlo simulation that samples heavy quarks using distributions from pQCD FONLL calculations [52,53], implements either a parameterized energy loss model+energy loss fluctuations or a Langevin model, and then this is followed by fragmentation functions and coalescence to obtain the final particle yields.…”
Section: Modelmentioning
confidence: 99%